2012
DOI: 10.1371/journal.pone.0046589
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Regulation of Glucose Metabolism and Cell-Cycle Progression in Mammalian Colonocytes

Abstract: A prodigious number of microbes inhabit the human body, especially in the lumen of the gastrointestinal (GI) tract, yet our knowledge of how they regulate metabolic pathways within our cells is rather limited. To investigate the role of microbiota in host energy metabolism, we analyzed ATP levels and AMPK phosphorylation in tissues isolated from germfree and conventionally-raised C57BL/6 mice. These experiments demonstrated that microbiota are required for energy homeostasis in the proximal colon to a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 32 publications
4
103
0
7
Order By: Relevance
“…Some 80% of ATP produced in colonocytes comes from mitochondrial oxidation of butyrate, which is derived from gut microbiota. However, experiments with germ-free mice have shown that, in the absence of microbiotaderived butyrate, colonocytes switch from burning butyrate to fermenting glucose to lactate (36). It is possible that the flushing action of diarrhea during dysentery removes much of the microbiota, thereby lowering butyrate levels in the colon and triggering colonocyte metabolism similar to HeLa cell metabolism in our in vitro model.…”
Section: Discussionmentioning
confidence: 94%
“…Some 80% of ATP produced in colonocytes comes from mitochondrial oxidation of butyrate, which is derived from gut microbiota. However, experiments with germ-free mice have shown that, in the absence of microbiotaderived butyrate, colonocytes switch from burning butyrate to fermenting glucose to lactate (36). It is possible that the flushing action of diarrhea during dysentery removes much of the microbiota, thereby lowering butyrate levels in the colon and triggering colonocyte metabolism similar to HeLa cell metabolism in our in vitro model.…”
Section: Discussionmentioning
confidence: 94%
“…For example, some metabolic end products of Bacteroidia and Clostridia, such as butyrate, confer benefit to the host by providing nutrition for colonocytes, which mitochondrially oxidize this compound to carbon dioxide [34] (Fig. 1A).…”
Section: Microbial Metabolism In the Healthy Large Intestinementioning
confidence: 99%
“…Hydrogen produced by Clostridia and Bacteroidia fuels the growth of sulfate-reducing bacteria ( Desulfovibrio ), which produce hydrogen sulfide [35-37], a toxic gas oxidized by colonocytes to form harmless thiosulfate [38,39]. Butyrate is a fermentation product of obligate anaerobic bacteria that serves as nutrient for colonocytes [34]. (B) The metabolic niche occupied by facultative anaerobic Enterobacteriaceae in the healthy intestine.…”
Section: Figurementioning
confidence: 99%
“…Butyrate in particular has potent effects on host tissues. As with other SCFAs, butyrate is consumed by the host as an energy source; however, unlike the other common SCFAs, such as propionate and acetate, butyrate is the preferred energy source for colonocytes (2) and is rapidly absorbed and used by the colonic epithelium. This rapid oxidation of butyrate reduces local oxygen concentrations, causing the epithelia to become hypoxic and thus limiting the growth of facultative aerobic pathogens, such as Salmonella species (3,4).…”
mentioning
confidence: 99%